Clinical characteristics and early treatment outcomes of follicular lymphoma in young adults. (22nd April 2015) - Gangatharan, Shane A.; Maganti, Manjula; Kuruvilla, John G.; Kukreti, Vishal; Tiedemann, Rodger E.; Gospodarowicz, Mary K.; Hodgson, David C.; Sun, Alex; Tsang, Richard W.; Pintilie, Melania; Crump, Michael
Summary Follicular lymphoma (FL) in young adults (YA, <40 years old) is uncommon, and the clinical characteristics and outcomes of this group are not well defined. We conducted a retrospective database review of 427 patients with newly diagnosed FL aged 65 years or less registered at Princess Margaret Cancer Centre between 1995 and 2010. YA (n = 61) and those 40–65 (n = 366) were compared with regards to clinical stage at diagnosis, FL International Prognostic Index (FLIPI) score, and the following clinical outcomes: time to second treatment, cause‐specific survival (CSS) and overall survival (OS). At diagnosis, stage and FLIPI score were similar, as were the proportion of patients requiring therapy (YA 75% versus older adults 71%). Median follow‐up was 8·1 years. Time to second therapy was similar in both age groups (5‐year probability 23% YA versus 27% older adults; Gray's P‐value = 0·76). Ten‐year OS was significantly higher for YA (87% versus older adults 72%; P = 0·029). On multivariate analysis, age <40 years, low FLIPI score and observation as initial management were favourable prognostic factors for OS and CSS. We conclude that YA with FL have a favourable prognosis compared to older patients; whether this reflects competing mortality risks or age‐related differences in lymphoma biology warrants further investigation.